CULTURAL DIPLOMACY THROUGH CUISINE: INTERNATIONAL STUDENTS’ PERSPECTIVE ON KIMCHI - Samantha, Audrey; Wulandari , Ida Suri (Jurnal Multidisipliner Bharasumba, 2025)
This study employs a descriptive qualitative approach to explore international students’ perceptions of kimchi. While many students are introduced to kimchi through Hallyu media or globalized Korean restaurants prior to arrival, their direct encounters in South Korea often reshape or challenge these expectations. Drawing on cultural discourse analysis and interview data, the research examines both the symbolic and sensory dimensions of kimchi. As a UNESCO-recognized cultural heritage, kimchi embodies resilience, collectivism, and Korean identity, yet its pungency and spiciness can pose challenges to adaptation. The findings suggest that food is not merely a source of sustenance but a cultural text that mediates identity, belonging, and diplomacy. By addressing both empirical and theoretical gaps in intercultural research, this study demonstrates that kimchi functions simultaneously as a cultural bridge and a boundary marker, underscoring the centrality of food in education and cultural diplomacy.